Kajian Meta-Analisis: Efektivitas Penggunaan Bahan Ajar terhadap Keterampilan Berpikir Kritis Berdasarkan Jenjang Pendidikan - Fitriani, Herdiyana; Sudiatmika, AAIA Rai; Suma, I Ketut; Suardana, I Nyoman (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Meta-analysis is a statistical method for combining quantitative results from several studies to produce an overall summary or empirical knowledge on a particular topic. This research aims to analyze the effectiveness of the use of teaching materials on students' critical thinking skills based on educational level. Research results that can be used in meta-analysis have certain characteristics/criteria. The analysis used is quantitative descriptive statistical analysis with the help of the OpenMEE application. Data analysis by calculating the Effect Size (ES) value from the mean value, Standard Deviation (SD), and number of samples (N) from each article analyzed. The overall average effect size is 3.801 in the high category (ES â‰¥ 0.8), and the P-Value value is <0.001, which means that the use of teaching materials provides significant effectiveness in critical thinking skills because the P-Value value is higher. smaller than 0.05. Meanwhile, the results of the heterogeneity test show that the TauË†2 value is 4.091, and the Het P-Value value is <0.001, which means it is significant. So it can be said that the Q statistic from the 17 studies has a variety of variances with diversity that is classified as very high with an IË†2 value reaching 97.1%, so there is potential for moderator variable analysis to be carried out. Furthermore, the effect size value based on level of education obtained an average effect size at the high school education level of 9.196, higher than other levels of education, which means that the use of teaching materials is more effective when used at the high school level compared to elementary, middle school and other educational levels. University, with P-Value < 0.001, which means that the use of teaching materials in high school provides significant effectiveness.